Advances in atomic oxygen resistant polyimide composite films. (May 2023) - Huang, Chuanjin; Liu, Jian; Zhao, Libin; Hu, Ning; Wei, Qiang
Abstract: Polyimide (PI) film is an attractive space material used in low Earth orbit (LEO) environment, owing to its extraordinary thermal, chemical stability, flexibility, excellent mechanical and insulating properties. These superior properties and versatility make PI one of the indispensable materials ensure the normal operation of spacecraft, which are unparalleled by most other polymers. Hydrocarbon-based PI, however, cannot withstand the erosion of atomic oxygen (AO) in LEO. Up to now, many strategies including coating, matrix modification and structural design have been utilized to improve the AO resistance of PI film. This review summarizes the state-of-the-art works on the PI composite films with AO resistance, and discusses the advantages and disadvantages of different strategies for protecting PI matrix from AO erosion. First, we discuss the conventional coatings protection, which contains inorganic, organic and organic–inorganic coatings. Then, the focus is attached to improving the inherent anti-AO capacity of PI film through matrix modifications, such as intrinsic, blending and doping modification strategies. Finally, the structural design strategies including Janus structure and bioinspired microstructure are also discussed. Fundamental parameters of PI composite films, such as mass loss, erosion yield, as well as mechanical properties, are highlighted to evaluate their anti-AO ability. Inspired by investigations over the past decades, a roadmap is also carefully depicted for the future of AO-resistant PI composite films in fundamental research.